2024
DOI: 10.3390/su16020691
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Media Data to Research the Impact of Campus Green Spaces on Students’ Emotions: A Case Study of Nanjing Campuses

Ao Wang,
Ziran Meng,
Bing Zhao
et al.

Abstract: Campus green space, as a component of urban green space and the main natural place for college students’ daily contact, has a subliminal effect on their mental health. This study aims to investigate the degree of influence of campus green space on college students’ emotions as well as the main indicators of influence and other scientific issues. Taking the campus green spaces of 44 college campuses in Nanjing as the object of the study, with the help of social media data to research the issue of green spaces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Overall, there was increased sensitivity and demand for green space during the pandemic [75], but categorizing the population revealed that not all groups had positive attitudes towards urban green spaces. According to demographic data, the population was categorized into three distinct segments: the "low-income" group, the "middle-class" group, and the "affluent" group, primarily based on income and educational qualifications.…”
Section: Green Space Preferences Across Diverse Social Groups Amidst ...mentioning
confidence: 99%
“…Overall, there was increased sensitivity and demand for green space during the pandemic [75], but categorizing the population revealed that not all groups had positive attitudes towards urban green spaces. According to demographic data, the population was categorized into three distinct segments: the "low-income" group, the "middle-class" group, and the "affluent" group, primarily based on income and educational qualifications.…”
Section: Green Space Preferences Across Diverse Social Groups Amidst ...mentioning
confidence: 99%